Seducing an angel - Balogh, Mary (Delacorte Press, 2009)
In glittering Regency England a desititute widow stands accused of murdering her husband and must now barter her beauty in order to survive. With seduction in mind, she sets her sights on Stephen Huxtable, the irresistibly attractive Earl of Merton and London's most eligible bachelor.